Indirect lightning performance of 10-kV overhead distribution lines - Yu, Jianli; Gu, Shanmao; Liu, Jianjun; Liu, He (Frontiers in Energy Research, 2024)
The lightning-induced voltage in 10-kV overhead distribution lines was calculated and analyzed using the Agrawal coupling model and second-order finite difference-time domain (FDTD) method. The influence of lightning position on lightning-induced voltage was analyzed using the concept of indirect lightning withstanding levels. To achieve the limiting effect on lightning-induced voltage in 10-kV lines, the installation density of surge arresters should not be less than 1 group per 200–300 m.